Matkaopas Haaparanta - Karunki - Ylitornio - Pello - Pajala - Junosuanto - Vittanki - Kiiruna - Vaskivuori - Jällivaara - Ylikainuu - Morajärvi - Alakainuu - Haaparanta - Markkanen, Kaarlo (tuntematon, 1937)
kuv., 13 x 18 cm